Peran Staf Tata Usaha dalam Pengelolaan Arsip di SMA Swasta Dharma Bhakti Siborongborong - Heddi Mariana Tampubolon; Ruslan Juliana Pardosi; Endang Juliati Manullang (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to understand the realization of archive management, the role of administrative staff in archive management, and the obstacles faced by administrative staff in archive management at SMA Swasta Dharma Bhakti Siborongborong, as well as the solutions provided. The approach used in this research is a descriptive approach with qualitative methods. Data can be obtained through observation, interviews, and documentation. Data analysis is carried out using data reduction techniques, data presentation, and conclusion drawing. The results of this research describe: (1) The realization of archive management includes the functions of planning, organizing, implementing, and supervising the administrative staff in archive management. (2) The role of administrative staff in serving and providing the necessary information to both internal and external parties of the school. (3) The obstacles faced by administrative staff in archive management include the lack of meticulousness of the administrative staff and the minimal archiving facilities. Therefore, the solution to improve archive management is to add archiving equipment in the administration office such as cabinets, archive racks, and folder maps, and the administrative staff should be more meticulous in storing documents.